Evaluation of the orientation of residential buildings in Mashhad based on direct solar radiation reception - Habibi, Mostafa; Azizibabani, Mohammadhossein (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
Reducing energy consumption and developing renewable energy sources are key strategies for addressing the environmental issues caused by fossil fuels. Cities consume 75% of the world's energy, with residential buildings being among the most energy-intensive sectors and offering significant potential for energy reduction. This paper evaluates the orientation of residential buildings in Mashhad based on direct solar radiation using EnergyPlus software. The analyses indicate that a vertical surface oriented at 220 degrees receives the highest radiation, while a vertical surface at 90 degrees receives the least annual direct radiation in Mashhad. During the hot seasons in Mashhad, south-facing façades receive 23% of the direct solar radiation received by horizontal surfaces, the lowest amount. Conversely, during the cold period, south-facing façades receive the highest direct solar radiation, 38% more than horizontal surfaces. Therefore, a south-facing orientation is the most effective during both the hot season (June, July, and August) and the cold period (November to March). Despite this, only 24% of Mashhad’s residential buildings are oriented towards the south, while the majority face southwest. After the south, the southwest orientation is the most suitable for Mashhad’s dominant cold periods. The southeast orientation, the second most common in Mashhad, is better suited for the hot seasons.